Analisis Pengaruh Lingkungan Sosial dan Financial Knowledge terhadap Minat Menggunakan Produk-produk Investasi Syariah: Studi Santri Siswa SMA IT Raudhatul Ulum Sakatiga Indralaya - Lisdayanti Hidayat, Lisdayanti Hidayat; Isni Andriana, Isni Andriana; Muizzudin, Muizzudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the influence of the social environment and financial knowledge on interest in using sharia investment products (study of students of Raudhatul Ulum Sakatiga Indralaya IT High School). This study used quantitative methods with questionnaires as research instruments. The population in this study amounted to 331 students with a sample of 182 respondents taken using the Non-Probability Sampling method with quota sampling techniques. The data analysis technique used in this study is multiple linear regression. Based on the results of the analysis, it is concluded that the social environment and financial knowledge have a positive and significant effect on the interest in using Islamic investment products.